Optimizing resilience in orofacial pain: a randomized controlled pilot study on hope - Emily J. Bartley; Natalie R. LaGattuta; Michael E. Robinson; Roger B. Fillingim (PAIN Reports, 2019)
Abstract. Introduction:. Over recent years, there has been growing interest in the role of positive, psychological resources that promote resilience and optimal functioning in chronic pain. Although multiple factors comprise resilience, hope is a strength-based motivational state known to contribute to positive psychosocial adjustment and adaptive pain coping. Emerging evidence supports the viability of therapeutic approaches that foster resilience; however, interventions designed to target hope in the context of pain have been remarkably understudied. Objectives:. The objectives of this pilot study were to test the feasibility and preliminary efficacy of a resilience-oriented hope intervention for clinical pain, as well as psychosocial outcomes and experimental pain sensitivity in individuals with orofacial pain. Methods:. Twenty-nine participants with temporomandibular disorder were randomized to a 3-session intervention intended to increase hope or a control intervention (EDU) involving education about pain and stress. Before and after the intervention, participants attended 2 laboratory sessions whereby they completed psychosocial questionnaires and sensitivity to heat, cold, and pressure pain was assessed. Hope was measured using the Adult State Hope Scale. Results:. Compared with EDU, the Hope group exhibited an increase in state hope, lower heat pain sensitivity, higher pressure pain thresholds at the temporomandibular joint, and reductions in pain catastrophizing. Conclusion:. Although preliminary, results suggest that a resilience-based hope intervention may be beneficial in reducing pain sensitivity and catastrophizing and could serve as a target for pain management.